A new species of Equinoxiodus (Dipnoi: ?Neoceratodontidae) from the Late Cretaceous of Brazil - Sousa, Eliane Pinheiro De; Medeiros, Manuel Alfredo; Toledo, Carlos Eduardo Vieira; Bertini, Reinaldo J.; Pereira, Agostinha Araújo; Lindoso, Rafael Matos (Zootaxa, 2015)
A noteworthy diversity of Dipnoi tooth plates has been collected in the fossiliferous conglomerates of the Alcântara Formation, early Cenomanian (Cretaceous) of Brazil. This sequence was deposited under transitional (estuarine) conditions, gathering reworked dissociated fossils represented by plants, fishes, crocodylomorphs, pterosaurs and dinosaurs. A new species of Dipnoi is reported in this work, Equinoxiodus schultzei sp. nov. whose genus is endemic of northern South America and lived probably in fresh water. The presence of several species of dipnoan in the mid-Cretaceous of north/northeastern Brazil indicates that the environmental conditions were very suitable to this group, confirming the well-marked seasonality of the climate, with frequent prolonged droughts, as interpreted in previous publications.